Can the Delhi Government’s ‘Mohalla’ clinic overcome its challenges and provide quality health services to the urban poor population? - KC, Bhuwan; Shankar, Pathiyil Ravi; Shrestha, Sunil (Journal of Karnali Academy of Health Sciences, 2019)
The ‘Mohalla’ clinics were set up by the Delhi state (provincial) government in India in 2014 to provide basic health services to people of Delhi city and its vicinity, especially targeting the urban poor. The Mohalla clinics are staffed by a doctor, a nurse, a pharmacist and a laboratory technician and theyprovide basic health services including immunisation, family planning and counselling services. The Mohalla clinic program had a good start and its operation was cost-effective; however, it is still struggling to increase its coverage to entire Delhi state as it had planned. The program got caught up in the central government and state government bureaucratic tussle, especially on the issue of acquiring land for setting up such clinics and on the implementation front due to the lack of operational plan and collaboration with the government line agencies. Thus, despite political will and funding a potentially viable urban health programmay have got stuck in the operational procedural complexities and political-bureaucratic tussle. This commentary article tries to discuss the challenges faced by the Delhi government’s ‘Mohalla’ clinics and a possible way forward to scale it up as a model urban health program.